Art’s histories in Aotearoa New Zealand - Jonathan Mané Wheoki (Journal of Art Historiography, 2011)
This is the text of an illustrated paper presented at ‘Art History’s History in Australia and New Zealand’; a joint symposium organised by the Australian Institute of Art History in the University of Melbourne and the Australian and New Zealand Association of Art Historians (AAANZ); held on 28 – 29 August 2010. Responding to a set of questions framed around the ‘state of art history in New Zealand’; this paper reviews the ‘invention’ of a nationalist art history and argues that there can be no coherent; integrated history of art in New Zealand that does not encompass the timeframe of the cultural production of New Zealand’s indigenous Maori; or that of the Pacific nations for which the country is a regional hub; or the burgeoning cultural diversity of an emerging Asia-Pacific nation.